“Key to the highway”: blues records and the great migration - Louis Mazzari (Transatlantica)
This paper looks at the way “race record” blues of the 1920s and 1930s reinforced the decision of poor farmers, sharecroppers, and working men and women to move to the cities of the North. The theme is the way black southerners used the blues as the soundtrack of the Great Migration. In a sense, the Delta blues was a musical travel narrative for tens of thousands of people who were leaving the rural South for an unknown, modern and industrial future. The paper will explore blues music as an expression of the fluidity of African American society and culture during the Great Depression.While avoiding direct protest, blues singers and musicians—first women, later men—crafted an art form and employed the technology of the phonograph to encourage freedom of movement and choice. At the moment the “race record” industry was being born, and black farmers and families were quietly picking up and leaving the South, the music they traveled with was the blues. The paper will look at examples of blues singers whose records dealt specifically with the Great Migration and consider their influence on listeners.